Cross-country analysis of digital content marketing in tourism - Bayraktar, Fetine (My University, 2024)
The main purpose of the paper is to evaluate the implications of DCM on the tourism market, specifically in different touristic regions. DCM is a digital inbound marketing strategy that aims to attract potential customers by producing innovative content and increasing their knowledge about services. The studies analyze the applications and outcomes of DCM strategies in the tourism market, highlighting the importance of digital marketing innovations for improving revenue in the sector. The study is based on a literature review of DCM in the tourism industry, using scientific articles from 2008 to 2023. The paper summarizes articles from selected journals to provide an overview of DCM in general. The research emphasizes the need for a cultural change in marketing approaches, shifting from \"selling\" to \"helping\" and utilizing social and electronic word of mouth in DCM. The papers provide theoretical and practical information for academics and businesses in the tourism industry, offering insights into the benefits and challenges of implementing DCM strategies. The studies also suggest the need for further research into digital content marketing, particularly in the context of B2B businesses.
Keywords: Tourism; Consumer Behavior; Digital Marketing; Digital Content Marketing; Content Creation